Optimising an underground mine cooling water operation - Jordan, Anastasiou (Stellenbosch : Stellenbosch University, 2025)
Anastasiou, J. 2025. Optimising an underground mine cooling water operation. Unpublished masters thesis. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/items/5ab1f703-165f-429d-a952-33d87a3c65ef